ANALISIS PENGARUH KESEIMBANGAN KEHIDUPAN KERJA DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PT NESTLE INDONESIA MEDAN REGION - Rio Samuel Pohan, Oki; Saladin Batubara, Soulthan; Anwar, Yohny (Universitas Muhammadiyah Tapanuli Selatan, 2024)
This study examines (1) the impact of work-life balance on employee performance at PT Nestlé Indonesia Medan Region, (2) the impact of internships on employee performance at PT Nestlé Indonesia Medan Region, and (3) the impact of work-life balance and internships on employee performance at PT Nestlé Indonesia Medan Region. This study was conducted using a quantitative approach. The target population of this study consisted only of employees of PT Nestlé Indonesia Medan Region, totaling 34 people. The number of respondents used in this study was based on saturated samples, encompassing all 34 employees. The data analysis technique employed was multiple linear regression. Researchers conducted the research using a questionnaire and performed statistical calculations using SPSS version 20. Based on the data obtained in this study and the results of hypothesis testing for each independent variable at a significance level of 5%, it was found that the influence of each independent variable on the dependent variable was negligible. The work-life balance variable had a significant effect on employee performance with a value of 0.584, while the communication variable had a significant effect on employee performance with a value of 0.146. It can be concluded that work-life balance and work organization significantly influence employee performance.